Curriculum and teaching dialogue. Volume 14, no. 1-2 - Flinders, David J.; Uhrmacher, P. Bruce (Emerald Publishing Limited, 2012)
Curriculum and Teaching Dialogue is the journal of the American Association of Teaching and Curriculum (AATC). An important historical event in the development of organizations dealing with the scholarly field of teaching and curriculum was the founding of the AATC on October 1, 1993. The members of the AATC believed that the time was long overdue to recognize teaching and curriculum as a basic field of scholarly study, to constitute a national learned society for the scholarly field of teaching and curriculum (teaching is the more inclusive concept; curriculum is an integral part of teaching-the 'what to teach' aspect). Since that AATC has produced scholarship in teaching and curriculum and serve the general public through its conferences, journals, and the interaction of its members. The purpose of the organization as originally defined in Article 1, Section 2 of the AATC Constitution: 'To promote the scholarly study of teaching and curriculum; all analytical and interpretive approaches that are appropriate for the scholarly study of teaching and curriculum shall be encouraged.' Curriculum and Teaching Dialogue seeks to fulfill that mission.
Includes index.
Published for American Association for Teaching and Curriculum.
Keywords: Curriculum planning.; Effective teaching.; Education -- Curricula.; Curriculum planning and development.; elektronické knihy; electronic books